1999
DOI: 10.1093/jnci/91.14.1241
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Penetrance of BRCA1 and BRCA2 Gene Mutations in Unselected Ashkenazi Jewish Women With Breast Cancer

Abstract: Approximately 12% of breast cancers in the Ashkenazi Jewish population are attributable to mutations in the BRCA1 or BRCA2 gene. Genetic testing may be useful when Jewish women with breast cancer are diagnosed before age 50 years or have a close relative with ovarian or early-onset breast cancer. An association between breast and prostate cancers was observed in our study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
183
3
6

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(208 citation statements)
references
References 26 publications
15
183
3
6
Order By: Relevance
“…Jewish women are at high risk from disease caused by major mutations. Although the risk to a woman from a Jewish multiplex family (Egan et al, 1996) or a Jewish family with a BRCA1/2 mutation (Fodor et al, 1998) is increased by a factor of 3 -4, and although Jewish women are also at higher risk from additional breast cancer risk factors (Swift et al, 1987), we found that a Jewish MZ co-twin's risk of becoming affected was increased only marginally more than that to Jewish women generally (Mack et al, 1985;Warner et al, 1999). Even among multiplex Jewish families with early cases, we could identify only a few with BRCA1/2 mutations.…”
Section: Discussionmentioning
confidence: 53%
“…Jewish women are at high risk from disease caused by major mutations. Although the risk to a woman from a Jewish multiplex family (Egan et al, 1996) or a Jewish family with a BRCA1/2 mutation (Fodor et al, 1998) is increased by a factor of 3 -4, and although Jewish women are also at higher risk from additional breast cancer risk factors (Swift et al, 1987), we found that a Jewish MZ co-twin's risk of becoming affected was increased only marginally more than that to Jewish women generally (Mack et al, 1985;Warner et al, 1999). Even among multiplex Jewish families with early cases, we could identify only a few with BRCA1/2 mutations.…”
Section: Discussionmentioning
confidence: 53%
“…It demonstrated that BRCA2 mutation carriers have a relative risk (RR) of PRCA of 4.65 rising to 7.33 below the age of 65 years and BRCA1 mutation carriers have an RR of PRCA of 1.82 under the age of 65 years (BCLC, 1999; Thompson et al, 2002). Similar data have been recorded in the AJ population (Struewing et al, 1997;Warner et al, 1999;Giusti et al, 2003), although smaller clinical studies have generally not demonstrated an increased frequency of founder BRCA1/2 mutations among Jewish men with PRCA (Lehrer et al, 1998;Hubert et al, 1999;Nastiuk et al, 1999;Vazina et al, 2000). In the current data set, six men were identified from a previous study conducted at The Institute of Cancer Research, as described in the Materials and Methods section.…”
Section: Discussionmentioning
confidence: 54%
“…Studies of breast cancer patients have indicated that it may be difficult to define mutation screening criteria among women with minimal or no family history (Malone et al, 1998). Furthermore, the carrier risks associated with the mutations may be highly variable, and population-based risk estimates have indicated much lower cancer risks than those obtained from multiplecase families and, therefore, lower predictive value of cancer for a positive mutation test result (Struewing et al, 1997;Fodor et al, 1998;Thorlacius et al, 1998;Warner et al, 1999). Accordingly, genetic screening would be of greatest benefit in families with high cancer risk, i.e.…”
Section: Discussionmentioning
confidence: 99%